Answer:
4.25
Step-by-step explanation:
5-3/4=4.25
sry if im wrong hope this helps
brainliest? please?
I cannot see a pictureesss
Answer:
for #14, x=10
Step-by-step explanation:
in the graph, 6x = 5x +10 so if x was 10 it would be 60 = 60 so x = 10
Answer:
b po sana po maka tulong
Step-by-step explanation:
pa brainliest po
Answer: (f•g)(x)=2x²+12x
Step-by-step explanation:
(f•g)(x) is the same as saying f(x)•g(x). Since we have f(x) and g(x), we can just multiply them together.
(f•g)(x)=2x(x+6) [distribute by FOIL]
(f•g)(x)=2x²+12x
Now, we know that (f•g)(x)=2x²+12x.